Analisis Gaya Bahasa Personifikasi Dalam Novel Cinta Suci Zahrana Karya Habiburrahman El Shirazy - SUDRAJAD, MUH. EDY (2016)
ABSTRAK The purpose of this study were: 1) to describe the style personified form contained in Holy Love Novel Zahrana Habiburrahman El Shirazy. 2) Describe the meaning of style personified contained in Holy Love Novel Zahrana Habiburrahman El Shirazy. This research was developed with descriptive qualitative method. Data were analyzed using methods agih and unified method. Agih method is a method of analysis tools that are in the decisive part of the language concerned itself. Unified method is a method of analysis tools determiner outside, apart, and does not become part of the language concerned. The result showed a few things that need to be served. Shape style personified contained in Holy Love Novel Zahrana Habiburrahman El Shirazy as many as 31 of data, each style data personification in Holy Love Novel Zahrana Habiburrahman El Shirazy depict the beauty of nature and background circumstances and events of the storyline. Meaning personification style of language contained in Holy Love Novel Zahrana Habiburrahman El Shirazy is to create value the beauty of the story in the novel make an analogy of inanimate objects act, act, and talk like human beings so that the story in the novel is more interesting and beautiful. Keywords: Style personified, Holy Love Novel Zahrana